EVALUASI IMPLEMENTASI PERMENDAGRI NO. 9 TAHUN 2009 PADA PENYERAHAN PRASARANA JALAN PERUMAHAN DI KOTA CILEGON - Anas, Anas; Riswanda, Riswanda; Cadith, Juliannes (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This article discusses the evaluation of the implementation of Minister of Home Affairs Regulation No. 9 of 2009 concerning the Procedure for Handover of Public Facilities, Infrastructure, and Utilities (PSU) in Cilegon City, focusing on road infrastructure. The main challenges identified include non-compliance by developers, weak government supervision, and a lack of coordination between stakeholders. According to data from the Cilegon City Housing and Settlement Area Office, 29 developers have not handed over PSUs in accordance with regulations. The research employs a qualitative method with an evaluative approach based on literature studies to assess the implementation of Regulation No. 9 of 2009 regarding the handover of PSUs. The findings reveal that developers' non-compliance is often due to weak sanctions and a lack of understanding of regulations. On the other hand, budget constraints and limited supervision resources hinder the local government's management of PSUs. This study recommends strengthening regulations with stricter sanctions, adequate budget allocation for supervision, and increased transparency through clear agreements between developers and the government. A more structured coordination mechanism is also necessary to accelerate the PSU handover process. The research contributes significantly to improving the implementation of PSU policies in Cilegon City to support better residential infrastructure and urban spatial planning.